Possibility of Simulating Forced Convection in Fast Neutron Reactors Using a Light Water Test Facility - Slobodchuk, V.I.; Avramova, E.A.; Shchennikova, E.M.; Shal'kov, D.A. (KnE Engineering, 2018)
The paper evaluates the possibility of modeling the heat transfer phenomena in a liquid-metal coolant using a light water test facility. A large nuclear power reactor (like the BN-1200 project) was selected as a reactor installation to be modeled. To validate the model, the similarity theory and the “black box” method were used. The paper uses the experience of a number of researchers in this field, in particular, the accepted assumptions which do not result in serious loss in modeling accuracy. The governing criteria of similarity were estimated based on the fundamental differential equations of convective heat transfer, so were the conditions under which it is possible to model sodium coolant by using light water with adequate accuracy. The paper presents the scales of the parameters used for the model - reactor comparison. Dependence curves of certain scales with regard to others are constructed, and the possibility of achieving similarity of certain parameters in modeling was estimated. Recommendations are provided on designing a water test model of the BN reactor and on carrying out experiments using this test model.